A Comparative Analysis of Morphological Characteristics between Endangered Local Prickly Pear and the Newly Introduced Dactylopius opuntiae-Resistant Species in Eastern Morocco - Ahmed Marhri; Mehdi Boumediene; Aziz Tikent; Reda Melhaoui; Kawtar Jdaini; Aatika Mihamou; Hana Serghini-Caid; Ahmed Elamrani; Christophe Hano; Malika Abid; Mohamed Addi (Scientifica)
Prickly pear serves as a significant source of income for farmers worldwide, with production taking place in temperate, subtropical, and cold regions. The objective of the present investigation is to explore the morphological parameters of Opuntia robusta and Opuntia dillenii which are resistant to the white cochineal (Dactylopius opuntiae), as well as the local prickly pear that is currently threatened with extinction. This investigation aims to evaluate the feasibility of replacing the endangered local prickly pear with the recently introduced species O. robusta and O. dillenii. This analysis is based on a comprehensive assessment of 26 qualitative and 25 quantitative traits pertaining to cladodes and fruits. In terms of species differentiation and the selection of discriminative features, this study demonstrates the effectiveness of various statistical methods, as well as the analysis carried out according to the descriptors recommended by the International Union for the Protection of New Varieties of Plants (UPOV). Of the 51 parameters evaluated, 13 qualitative and 23 quantitative characters are significant in differentiating the species under study. This underscores the importance of quantitative traits in distinguishing different prickly pear species. Furthermore, color is identified as a crucial characteristic for discriminating between the studied samples. O. robusta is characterized by its high fruit weight, large size, greater pulp content, and high pulp-to-peel ratio, all of which are desirable traits for fresh consumption. Additionally, O. robusta has the highest number of fully developed seeds, making it an attractive option for use in the cosmetic industry. This characteristic renders the O. robusta a potential substitute for the endangered ecotype . However, O. robusta is distinguished by its short stalk, which poses a challenge for fruit harvesting and leaves it susceptible to physical damage and quality loss. Conversely, O. dillenii displays a low pulp content, which serves as a critical indicator of fruit quality. The only desirable agronomic trait of this species is its elevated seed content, which has the potential for utilization in oil production for the cosmetic industry.